Rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating and preparation method thereof

By introducing rare earth Y2O3 into laser cladding technology, the interface combination between Ni-based alloy powder and SiC particles is improved, and the problem of insufficient bonding between ceramic particles and metal matrix is ​​solved, and the wear resistance and overall performance of the coating are significantly improved.

CN119640260APending Publication Date: 2025-03-18CHANGAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868657.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When the existing laser cladding technology prepares metal cermet composite coatings, the interface bond between the ceramic particles and the metal matrix is ​​insufficient, resulting in thermal stresses easily generated inside the coating, causing defects such as peeling, cracks and pores, affecting the mechanical properties and durability of the coating.

Method used

By introducing rare earth Y2O3, Ni-based alloy powder, SiC particles and other alloy elements are ball milled to improve the uniformity and wettability of the powder, and a dense wear-resistant coating is prepared on the surface of the substrate using laser cladding technology.

Benefits of technology

It effectively improves the interface combination between ceramic particles and metal matrix, reduces internal defects of the coating, and improves the wear resistance, density and overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640260A_ABST
    Figure CN119640260A_ABST
Patent Text Reader

Abstract

The invention relates to the field of laser cladding metal ceramic composite materials, and discloses a preparation method of a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, which is characterized by comprising the following steps: S10, powder preparation: carrying out ball milling and mixing on Ni-based alloy powder, SiC particles, alloy elements such as C, B, Cr, Si, Mo and the like which are added according to a certain proportion and rare earth Y2O3 to obtain powder; uniform dispersion of the powder is ensured, and drying treatment is performed to prevent the powder from caking; and S20, base material pretreatment is conducted, specifically, the surface of the steel base material is polished step by step through 180 # abrasive paper, 400 # abrasive paper and 600 # abrasive paper, oxide skin and a rough layer are removed, then cleaning is conducted through absolute ethyl alcohol and acetone, and the clean and greasy-dirt-free base material surface is obtained. According to the rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating and the preparation method thereof, the interface bonding between ceramic particles and a metal matrix is improved by introducing rare earth, and the internal defects of the cladding layer are reduced, so that the wear resistance and the overall performance of the coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of laser cladding metal-ceramic composite materials, in particular to a rare earth-containing SiC particle-reinforced Ni-based wear-resistant laser cladding coating and a preparation method thereof. Background Art

[0002] In the vast field of industrial production, the problem of surface wear of metal materials is particularly prominent. It is not only the culprit of the performance degradation of mechanical parts, but also a major source of resource consumption and economic losses. From precision instruments to heavy machinery, all face the challenges of performance degradation and shortened life due to friction and wear. Surface treatment technology is a key means to improve the wear resistance of metal materials. Through physical, chemical or composite methods, one or more layers of coatings or modified layers with excellent wear resistance are constructed on the surface of the material, which effectively isolates the direct contact between the substrate and the environment, significantly reduces the wear rate, and extends the service life of the equipment. This not only reduces the unnecessary loss of metal materials, but also promotes the sustainable use of resources, injects green power into industrial development, and effectively curbs the economic losses caused by wear.

[0003] Laser cladding technology, as a cutting-edge surface modification method, has shown great potential in improving the mechanical properties of metal substrate surfaces and has demonstrated its economic efficiency by reducing the consumption of precious metals. However, this technology still faces several significant defects and shortcomings in practical applications. The primary problem is that although Ni-based alloys are widely used in laser cladding due to their good wettability, toughness and high bonding strength, in the application of composite materials, especially when high-melting-point ceramic particles such as carbides, nitrides, borides and oxides are added to the alloy powder system to form metal-ceramic composite coatings, the huge differences in physical and chemical properties between materials have become a major challenge. Specifically, ceramic reinforcement phases such as SiC have excellent high Melting point, high hardness, corrosion resistance and oxidation resistance are regarded as ideal additives to improve coating performance. However, the poor wettability between these ceramic particles and the metal matrix, the mismatch of thermal expansion coefficients, and the huge difference in melting points lead to large thermal stresses inside the cladding layer during the rapid heating and cooling process of laser cladding, which in turn causes defects such as spalling, cracks and pores. These defects not only seriously weaken the mechanical properties and durability of the coating, but may also cause damage to the matrix material, affecting the safety and reliability of the overall component. Therefore, when preparing metal-ceramic composite coatings, the existing laser cladding technology urgently needs to solve the interface bonding problem between ceramic particles and the metal matrix, as well as the internal defects of the coating caused by this. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] The purpose of the present invention is to improve the interface bonding between ceramic particles and metal matrix by introducing rare earth, reduce internal defects of cladding layer, thereby improving the wear resistance and overall performance of coating, and propose a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating and its preparation method.

[0006] (II) Technical solution

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, characterized in that it comprises the following steps:

[0009] S10, powder preparation, ball milling and mixing Ni-based alloy powder, SiC particles, and alloy elements such as C, B, Cr, Si, Mo, and rare earth Y2O3 added in a certain proportion to ensure that the powder is evenly dispersed, and drying to prevent the powder from agglomerating;

[0010] S20, substrate pretreatment, using 180#, 400#, 600# sandpaper to polish the steel substrate surface step by step to remove the oxide scale and rough layer, and then cleaning with anhydrous ethanol and acetone to obtain a clean and oil-free substrate surface;

[0011] S30, powder coating, using a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a specific ratio, evenly coating the mixed powder on the surface of the substrate, and then air-drying it naturally for 24 hours;

[0012] S40, laser cladding, set the laser process parameters, including laser power 1200-2000W, scanning speed 6-8mm / s, overlap rate 45%, spot diameter 2mm, use Ar gas protection, and prepare a dense wear-resistant coating on the substrate surface through laser cladding technology.

[0013] Based on the above technical solution, the present invention can also be improved as follows.

[0014] Furthermore, the step S10 specifically includes the following steps:

[0015] S101, material preparation, accurately weighing Ni-based alloy powder, SiC particles, C, B, Cr, Si, Mo and other alloy element powders and rare earth Y2O3 according to the predetermined mass percentage, ensuring that all materials are of high purity to avoid the influence of impurities on the coating performance;

[0016] S102, ball milling and mixing, putting weighed various powder materials into a ball mill, adding an appropriate amount of ball milling media such as stainless steel balls or ceramic balls, setting parameters such as the speed of the ball mill, ball milling time and ball-to-material ratio, generally, the speed of the ball mill will affect the degree of powder refinement and mixing uniformity, and the ball milling time determines the degree of mixing sufficiency, starting the ball mill for mixing, during the ball milling process, collision and friction occur between the ball milling media and the powder, so that the powder is gradually refined and evenly mixed, and the ball milling effect is regularly checked to ensure that the powder is evenly mixed and reaches the required particle size requirements;

[0017] S103, drying treatment, taking out the mixed powder after ball milling from the ball mill jar and drying it. The purpose of drying is to remove moisture and other volatile substances in the powder to prevent the powder from agglomerating during subsequent processing. The drying treatment can be carried out in an oven, and appropriate temperature and time are set. The temperature should not be too high to avoid oxidation or deterioration of the powder; the time should be long enough to ensure that the powder is completely dry. The dried powder should be stored in a dry, cool, ventilated place to avoid moisture and contamination;

[0018] S104, quality inspection, conduct quality inspection on the mixed powder after drying, including indicators such as particle size distribution, mixing uniformity, and impurity content. If necessary, the powder can be screened or ball-milled again to meet the requirements of subsequent processing.

[0019] Furthermore, the percentage composition of each part in step S101 is: C: 0.4-0.7wt.%, B: 2.5-2.7wt.%, Cr: 15-17wt.%, Si: 4-4.5wt.%, Mo: 2.6-3wt.%, SiC: 10-30wt.%, and the remainder is Ni, wherein the addition amount of Y2O3 is 0.4-1.6wt.% of the total mass of the alloy powder.

[0020] Furthermore, the particle size range of the alloy element powder is 45-100 μm, and the particle size range of Y2O3 is 1-3 μm.

[0021] Furthermore, the step S20 specifically includes the following steps:

[0022] S201, preliminary grinding, use 180# sandpaper to perform preliminary grinding on the surface of Q345 steel substrate. This step is mainly to remove large particles of impurities, thick oxide scale and obvious rough layer on the surface. When grinding, the force should be uniform and carried out in a certain direction to avoid leaving obvious scratches on the surface of the substrate;

[0023] S202, medium grinding. After the initial grinding, use 400# sandpaper for medium grinding. The purpose of this step is to further refine the surface of the substrate and remove the fine scratches and residual oxide skin left in the previous step. It is also necessary to maintain uniform strength and consistent direction for grinding.

[0024] S203, fine grinding, use 600# sandpaper for fine grinding. This step is to obtain a smoother and cleaner substrate surface, providing a good foundation for subsequent coating adhesion. When fine grinding, special attention should be paid to controlling the strength and speed to avoid excessive grinding and causing damage to the substrate surface;

[0025] S204, degreasing and cleaning. After polishing, impurities such as oil, dust, etc. may remain on the surface of the substrate. First, use anhydrous ethanol to clean the surface of the substrate to remove oil and organic impurities. Anhydrous ethanol has good solubility and volatility, and can quickly and effectively remove oil without leaving any residue on the surface of the substrate.

[0026] S205, deep cleaning, use acetone to deep clean the surface of the substrate. Acetone can further remove tiny impurities and residues on the surface to ensure that the surface of the substrate is clean and free of dirt. When cleaning, use a soft cloth or cotton swab to dip in an appropriate amount of acetone and gently wipe the surface of the substrate. Be careful not to use excessive force to scratch the surface of the substrate;

[0027] S206. Drying treatment: After cleaning, the substrate should be placed in a ventilated place to dry naturally, or clean compressed air should be used to blow dry the surface moisture. Only after the substrate surface is completely dry can subsequent coating treatment be carried out.

[0028] Furthermore, in step S20, the steel substrate is Q345 steel.

[0029] Furthermore, the step S30 specifically includes the following steps:

[0030] S301, preparing the binder. First, two main materials, ethyl cellulose and anhydrous ethanol, need to be prepared. Ethyl cellulose is the main component of the binder, and anhydrous ethanol is the solvent. The amounts of ethyl cellulose and anhydrous ethanol are accurately calculated according to specific ratio requirements. This ratio is the key to ensure stable performance of the binder and good coating effect. The calculated ethyl cellulose is gradually added to the anhydrous ethanol while stirring until the ethyl cellulose is completely dissolved to form a uniform and transparent binder solution.

[0031] S302, powder mixing, prepare the powder material to be coated and ensure that it is mixed evenly without agglomeration, gradually add the prepared binder solution to the powder, stir with an appropriate tool such as a stirrer while adding, so that the powder and the binder are fully mixed evenly, and the stirring speed and time should be controlled during the mixing process to avoid generating too many bubbles or destroying the powder particles;

[0032] S303, apply powder, ensure that the surface of the substrate has been pre-treated, clean, flat and free of oil. If there is dust or impurities on the surface of the substrate, it should be cleaned with a clean cloth or compressed air first, and use appropriate coating tools such as brushes, spray guns, etc. to evenly apply the mixed powder on the surface of the substrate. When applying, a certain thickness and uniformity should be maintained to avoid missing or uneven thickness. For large-area or complex-shaped substrates, multiple coatings or coating at different angles may be required to ensure the coating effect;

[0033] S304, natural air drying, place the powder coated substrate in a well-ventilated place away from direct sunlight for natural air drying, ensure the air drying environment is clean and dust-free to avoid contamination of the coating. According to the requirements, the substrate is naturally air dried for 24 hours. This time is the key to ensure that the coating is fully dried, cured and reaches the predetermined performance. During the air drying process, the state of the coating should be checked regularly to ensure that there is no cracking, peeling, etc.

[0034] Furthermore, the ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1:10, wherein the coating thickness is 1-1.5 mm.

[0035] Furthermore, the step S40 specifically includes the following steps:

[0036] S401. In the preparation stage, ensure that the laser, gas protection system and other equipment are in good working condition without faults or abnormalities. According to the characteristics of the coating material and the substrate, set the power of the laser in the range of 1200-2000W. The specific value needs to be determined based on experiments or experience to achieve the best cladding effect. Set the scanning speed to 6-8mm / s. This speed range can ensure that the laser beam moves evenly on the surface of the substrate, while fully melting the powder and combining it with the substrate. Set the overlap rate to 45%. The overlap rate refers to the overlap between adjacent cladding passes, which is very important for ensuring the uniformity and density of the coating. Set the spot diameter to 2mm. The size of the spot directly affects the distribution of laser energy and the width of the cladding layer. Connect the Ar gas source and adjust the gas flow rate to an appropriate value to ensure that the cladding area is fully protected to prevent oxidation and impurity contamination.

[0037] S402, laser cladding operation, according to the specific requirements of the coating material and the substrate, the substrate is preheated. Preheating can reduce the thermal stress in the cladding process and improve the bonding strength between the coating and the substrate, but preheating is not required in all cases. Start the laser according to the set process parameters, focus the laser beam on the substrate surface, the laser beam heats the substrate surface and the powder material, causing them to melt and mix rapidly, and the molten material solidifies rapidly on the substrate surface to form a dense, wear-resistant coating. Control the movement path and speed of the laser beam to ensure that the coating is uniform and defect-free. Perform multiple cladding passes according to the set overlap rate to ensure the thickness and uniformity of the coating. Monitoring and adjustment: During the cladding process, the cladding quality is monitored in real time through the control system to observe whether the coating surface is flat and whether there are defects such as cracks or pores. If necessary, adjust the laser process parameters in time to ensure the quality of the cladding layer. After the cladding is completed, let the coating cool naturally or use appropriate cooling methods to accelerate the solidification process. The control of the cooling rate has a certain influence on the performance of the coating and needs to be determined according to the specific situation.

[0038] S403, follow-up treatment, clean the residual powder and impurities around the cladding area, check whether the coating surface is smooth and defect-free, and perform performance tests on the cladding coating, such as hardness, wear resistance, corrosion resistance, etc., to verify whether it meets the design requirements.

[0039] A rare earth-containing SiC particle-reinforced Ni-based wear-resistant laser cladding coating is prepared by the above-mentioned preparation method.

[0040] (III) Beneficial effects

[0041] Compared with the prior art, the technical solution of this application has the following beneficial technical effects:

[0042] In the powder preparation stage, Ni-based alloy powder, SiC particles, and alloy elements such as C, B, Cr, Si, Mo and rare earth Y2O3 added in proportion are fully mixed by ball milling, and the powder is ensured to be evenly dispersed. The addition of rare earth Y2O3 is one of the cores of the present invention. It can not only effectively improve the wettability between SiC particles and Ni-based alloys, but also optimize the microstructure of the coating by refining grains, purifying the melt and the like. In addition, the introduction of alloy elements such as C, B, Cr, Si, Mo can further enhance the hardness, toughness and wear resistance of the coating, so that it has more comprehensive mechanical properties. The drying treatment effectively prevents powder agglomeration and provides high-quality raw materials for subsequent steps. Secondly, in the substrate pretreatment stage, the oxide scale, rough layer and oil stain on the surface of the steel substrate are completely removed through step-by-step grinding and cleaning processes, and a clean and pollution-free substrate surface is obtained. This step is crucial to improving the bonding strength between the coating and the substrate, and lays a solid foundation for the good adhesion of the subsequent coating. Next, in the powder coating stage, a binder prepared by ethyl cellulose and anhydrous ethanol is used to The evenly mixed powder is evenly coated on the surface of the substrate and naturally air-dried. This step ensures the uniform distribution and preliminary fixation of the powder on the surface of the substrate, providing a stable powder layer for subsequent laser cladding. Finally, in the laser cladding stage, by accurately setting the process parameters of the laser, including laser power, scanning speed, overlap rate and spot diameter, and using Ar gas protection, a dense wear-resistant coating was successfully prepared on the surface of the substrate. The addition of rare earth Y2O3 played a key role in this process. It promoted the uniform diffusion and bonding between the elements in the molten pool, and effectively reduced the defects such as peeling, cracks and pores caused by uneven thermal stress. At the same time, the optimized process parameters ensured the stability and controllability of the cladding process, and further improved the density and wear resistance of the coating. In summary, by introducing rare earth Y2O3 and finely controlling the process parameters of each step, the defects faced by the laser cladding technology mentioned in the background technology in the preparation of metal-ceramic composite coatings were effectively solved, and the wear resistance, density and interface bonding of the coating were significantly improved, providing a new solution for the surface protection of mechanical equipment and parts in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The microstructure of the cladding coating obtained in Example 1 is shown in FIG. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention provides a method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, comprising the following steps:

[0046] S10, powder preparation, ball milling and mixing Ni-based alloy powder, SiC particles, and alloy elements such as C, B, Cr, Si, Mo, and rare earth Y2O3 added in a certain proportion to ensure that the powder is evenly dispersed, and drying to prevent the powder from agglomerating;

[0047] Step S10 specifically includes the following steps:

[0048] S101, material preparation, accurately weighing Ni-based alloy powder, SiC particles, C, B, Cr, Si, Mo and other alloy element powders and rare earth Y2O3 according to the predetermined mass percentage, ensuring that all materials are of high purity to avoid the influence of impurities on the coating performance;

[0049] S102, ball milling and mixing, putting weighed various powder materials into a ball mill, adding an appropriate amount of ball milling media such as stainless steel balls or ceramic balls, setting parameters such as the speed of the ball mill, ball milling time and ball-to-material ratio, generally, the speed of the ball mill will affect the degree of powder refinement and mixing uniformity, and the ball milling time determines the degree of mixing sufficiency, starting the ball mill for mixing, during the ball milling process, collision and friction occur between the ball milling media and the powder, so that the powder is gradually refined and evenly mixed, and the ball milling effect is regularly checked to ensure that the powder is evenly mixed and reaches the required particle size requirements;

[0050] S103, drying treatment, taking out the mixed powder after ball milling from the ball mill jar and drying it. The purpose of drying is to remove moisture and other volatile substances in the powder to prevent the powder from agglomerating during subsequent processing. The drying treatment can be carried out in an oven, and appropriate temperature and time are set. The temperature should not be too high to avoid oxidation or deterioration of the powder; the time should be long enough to ensure that the powder is completely dry. The dried powder should be stored in a dry, cool, ventilated place to avoid moisture and contamination;

[0051] S104, quality inspection, quality inspection of the mixed powder after drying, including indicators such as particle size distribution, mixing uniformity, impurity content, etc. If necessary, the powder can be screened or ball-milled again to meet the requirements of subsequent processing;

[0052] The percentage composition of each part in step S101 is: C: 0.4-0.7wt.%, B: 2.5-2.7wt.%, Cr: 15-17wt.%, Si: 4-4.5wt.%, Mo: 2.6-3wt.%, SiC: 10-30wt.%, and the balance is Ni, wherein the addition amount of Y2O3 is 0.4-1.6wt.% of the total mass of the alloy powder;

[0053] The particle size range of the alloy element powder is 45-100 μm, and the particle size range of Y2O3 is 1-3 μm;

[0054] Through precise material preparation, high-purity Ni-based alloy powder, SiC particles, alloy element powder and rare earth Y2O3 are accurately weighed according to the predetermined mass percentage, effectively avoiding the adverse effects of impurities on coating performance and ensuring the purity and consistency of coating composition. Subsequently, in the ball milling mixing stage, the speed, time and ball-to-material ratio of the ball mill are finely controlled to achieve full refinement and uniform mixing of the powder. This process not only improves the activity of the powder and promotes the diffusion and reaction of elements in the subsequent cladding process, but also significantly improves the wettability between SiC particles and Ni-based alloy, providing favorable conditions for the formation of a dense interface bond. Conditions, drying treatment further removes moisture and volatile substances in the powder, prevents powder agglomeration, and ensures the stability and fluidity of the powder in subsequent processing. This step is of great significance for maintaining the original properties of the powder and avoiding deterioration during storage and transportation. Finally, quality inspection ensures that the mixed powder meets the predetermined requirements of particle size distribution, mixing uniformity and impurity content, providing reliable guarantee for the preparation of high-quality wear-resistant coatings, especially the particle size range regulations for alloy element powders and Y2O3, which further refines the specifications of raw materials and helps to achieve a finer coating structure and better performance.

[0055] S20, substrate pretreatment, using 180#, 400#, 600# sandpaper to polish the steel substrate surface step by step to remove the oxide scale and rough layer, and then cleaning with anhydrous ethanol and acetone to obtain a clean and oil-free substrate surface;

[0056] The step S20 specifically includes the following steps:

[0057] S201, preliminary grinding, use 180# sandpaper to perform preliminary grinding on the surface of Q345 steel substrate. This step is mainly to remove large particles of impurities, thick oxide scale and obvious rough layer on the surface. When grinding, the force should be uniform and carried out in a certain direction to avoid leaving obvious scratches on the surface of the substrate;

[0058] S202, medium grinding. After the initial grinding, use 400# sandpaper for medium grinding. The purpose of this step is to further refine the surface of the substrate and remove the fine scratches and residual oxide skin left in the previous step. It is also necessary to maintain uniform strength and consistent direction for grinding.

[0059] S203, fine grinding, use 600# sandpaper for fine grinding. This step is to obtain a smoother and cleaner substrate surface, providing a good foundation for subsequent coating adhesion. When fine grinding, special attention should be paid to controlling the strength and speed to avoid excessive grinding and causing damage to the substrate surface;

[0060] S204, degreasing and cleaning. After polishing, impurities such as oil, dust, etc. may remain on the surface of the substrate. First, use anhydrous ethanol to clean the surface of the substrate to remove oil and organic impurities. Anhydrous ethanol has good solubility and volatility, and can quickly and effectively remove oil without leaving any residue on the surface of the substrate.

[0061] S205, deep cleaning, use acetone to deep clean the surface of the substrate. Acetone can further remove tiny impurities and residues on the surface to ensure that the surface of the substrate is clean and free of dirt. When cleaning, use a soft cloth or cotton swab to dip in an appropriate amount of acetone and gently wipe the surface of the substrate. Be careful not to use excessive force to scratch the surface of the substrate;

[0062] S206, Drying treatment: After cleaning, the substrate should be placed in a ventilated place to dry naturally, or use clean compressed air to blow dry the surface moisture. Only after the substrate surface is completely dry can the subsequent coating treatment be carried out;

[0063] In step S20, the steel substrate is Q345 steel;

[0064] The initial grinding removed the large particles of impurities, thick oxide scale and obvious rough layer on the surface, laying the foundation for subsequent processing. Then, the medium grinding and fine grinding gradually refined the surface of the substrate, removed the scratches and residues left in the previous step, and finally obtained a smooth and clean substrate surface. This step-by-step grinding method not only improved the flatness of the substrate surface, but also enhanced the bonding force between the coating and the substrate, reducing the risk of coating peeling. In the cleaning stage, degreasing cleaning uses the solubility and volatility of anhydrous ethanol to quickly and effectively remove oil and organic impurities on the surface of the substrate, laying the foundation for subsequent deep cleaning. The first step is to wash the substrate, and then deep clean with acetone to further remove tiny impurities and residues on the surface, ensuring the absolute cleanliness of the substrate surface. This double cleaning mechanism ensures that the substrate surface is free of oil, dust and residue, providing the best conditions for the adhesion of the coating. Finally, the drying treatment ensures that the substrate surface is in a completely dry state before subsequent coating treatment. This step avoids coating quality problems caused by residual moisture, such as pores and cracks. At the same time, natural drying or drying with clean compressed air also avoids deformation or performance degradation of the substrate caused by high temperature treatment.

[0065] S30, powder coating, using a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a specific ratio, evenly coating the mixed powder on the surface of the substrate, and then air-drying it naturally for 24 hours;

[0066] The step S30 specifically includes the following steps:

[0067] S301, preparing the binder. First, two main materials, ethyl cellulose and anhydrous ethanol, need to be prepared. Ethyl cellulose is the main component of the binder, and anhydrous ethanol is the solvent. The amounts of ethyl cellulose and anhydrous ethanol are accurately calculated according to specific ratio requirements. This ratio is the key to ensure stable performance of the binder and good coating effect. The calculated ethyl cellulose is gradually added to the anhydrous ethanol while stirring until the ethyl cellulose is completely dissolved to form a uniform and transparent binder solution.

[0068] S302, powder mixing, prepare the powder material to be coated and ensure that it is mixed evenly without agglomeration, gradually add the prepared binder solution to the powder, stir with an appropriate tool such as a stirrer while adding, so that the powder and the binder are fully mixed evenly, and the stirring speed and time should be controlled during the mixing process to avoid generating too many bubbles or destroying the powder particles;

[0069] S303, apply powder, ensure that the surface of the substrate has been pre-treated, clean, flat and free of oil. If there is dust or impurities on the surface of the substrate, it should be cleaned with a clean cloth or compressed air first, and use appropriate coating tools such as brushes, spray guns, etc. to evenly apply the mixed powder on the surface of the substrate. When applying, a certain thickness and uniformity should be maintained to avoid missing or uneven thickness. For large-area or complex-shaped substrates, multiple coatings or coating at different angles may be required to ensure the coating effect;

[0070] S304, natural air drying, place the powder coated substrate in a well-ventilated place away from direct sunlight for natural air drying, ensure that the air drying environment is clean and dust-free to avoid contamination of the coating. According to the requirements, the substrate is naturally air dried for 24 hours. This time is the key to ensure that the coating is fully dried, cured and reaches the predetermined performance. During the air drying process, the coating status should be checked regularly to ensure that there is no cracking, peeling, etc.;

[0071] The ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1:10, wherein the coating thickness is 1-1.5 mm;

[0072] In step S30, by carefully preparing the binder, mixing the powders, coating the powders and naturally drying the powders, the powders are evenly and stably coated on the surface of the substrate, which lays a solid foundation for the subsequent laser cladding process. First, the precise preparation of the binder ensures the stability of its performance and the good coating effect. Ethyl cellulose and anhydrous ethanol are prepared in a ratio of 1:10, which not only ensures the viscosity of the binder, but also facilitates operation and control. This ratio of binder can effectively adhere the powder to the surface of the substrate without affecting the diffusion and reaction of the elements in the subsequent laser cladding process. Secondly, in the powder mixing process, the binder is gradually added and fully stirred to ensure the uniform mixing of the powder and the binder, and avoid the generation of lumps and bubbles, which not only improves The uniformity and density of the coating also reduce the formation of internal defects in the coating. In the powder coating stage, by selecting appropriate coating tools and methods, the uniform coating of the powder on the substrate surface is ensured. Especially for substrates with large areas or complex shapes, multiple coatings or coating methods at different angles ensure the integrity and consistency of the coating. At the same time, the pretreatment and cleaning requirements of the substrate surface also further improve the adhesion and quality of the coating. Finally, the natural air-drying process provides the necessary time and environmental conditions for the full drying and curing of the coating. The 24-hour natural air-drying time ensures that the solvent in the coating is completely volatilized and the binder is fully cured, thereby improving the strength and wear resistance of the coating. At the same time, regular inspection of the coating status also ensures the integrity and defect-free nature of the coating.

[0073] S40, laser cladding, setting the laser process parameters, including laser power 1200-2000W, scanning speed 6-8mm / s, overlap rate 45%, spot diameter 2mm, using Ar gas protection, and preparing a dense wear-resistant coating on the surface of the substrate through laser cladding technology. The laser model is SLG-S6000;

[0074] The step S40 specifically includes the following steps:

[0075] S401. In the preparation stage, ensure that the laser, gas protection system and other equipment are in good working condition without faults or abnormalities. According to the characteristics of the coating material and the substrate, set the power of the laser in the range of 1200-2000W. The specific value needs to be determined based on experiments or experience to achieve the best cladding effect. Set the scanning speed to 6-8mm / s. This speed range can ensure that the laser beam moves evenly on the surface of the substrate, while fully melting the powder and combining it with the substrate. Set the overlap rate to 45%. The overlap rate refers to the overlap between adjacent cladding passes, which is very important for ensuring the uniformity and density of the coating. Set the spot diameter to 2mm. The size of the spot directly affects the distribution of laser energy and the width of the cladding layer. Connect the Ar gas source and adjust the gas flow rate to an appropriate value to ensure that the cladding area is fully protected to prevent oxidation and impurity contamination.

[0076] S402, laser cladding operation, according to the specific requirements of the coating material and the substrate, the substrate is preheated. Preheating can reduce the thermal stress in the cladding process and improve the bonding strength between the coating and the substrate, but preheating is not required in all cases. Start the laser according to the set process parameters, focus the laser beam on the substrate surface, the laser beam heats the substrate surface and the powder material, causing them to melt and mix rapidly, and the molten material solidifies rapidly on the substrate surface to form a dense, wear-resistant coating. Control the movement path and speed of the laser beam to ensure that the coating is uniform and defect-free. Perform multiple cladding passes according to the set overlap rate to ensure the thickness and uniformity of the coating. Monitoring and adjustment: During the cladding process, the cladding quality is monitored in real time through the control system to observe whether the coating surface is flat and whether there are defects such as cracks or pores. If necessary, adjust the laser process parameters in time to ensure the quality of the cladding layer. After the cladding is completed, let the coating cool naturally or use appropriate cooling methods to accelerate the solidification process. The control of the cooling rate has a certain influence on the performance of the coating and needs to be determined according to the specific situation.

[0077] S403, follow-up treatment, clean the residual powder and impurities around the cladding area, check whether the coating surface is smooth and defect-free, and perform performance tests on the cladding coating, such as hardness, wear resistance, corrosion resistance, etc., to verify whether it meets the design requirements;

[0078] Through the meticulous preparation stage, the good working condition of each equipment and the precise setting of process parameters during the laser cladding process are ensured. The precise setting of key parameters such as laser power, scanning speed, overlap rate and spot diameter directly determines the stability of the cladding process and the quality of the coating. In particular, the setting of laser power and scanning speed fully considers the characteristics of the coating material and the substrate, aiming to achieve the best cladding effect and improve the uniformity and density of the coating. The control of the overlap rate ensures the effective overlap between adjacent cladding passes, further enhancing the overall performance of the coating. At the same time, by connecting the Ar gas source and adjusting the gas flow rate, the oxidation and impurity contamination of the cladding area are effectively prevented, ensuring the purity and corrosion resistance of the coating. Secondly, during the laser cladding operation stage, the substrate is preheated to reduce the risk of corrosion during the cladding process. The thermal stress is reduced, and the bonding strength between the coating and the substrate is improved. Although this step is not necessary, it can significantly improve the coating quality under certain circumstances. In addition, the cooperation of the laser beam ensures the rapid melting of the powder material under the action of the laser beam and the full bonding with the substrate, forming a dense and wear-resistant coating. At the same time, through the monitoring and adjustment steps, the problems that may occur in the cladding process, such as uneven coating surface, cracks or pores, are discovered and corrected in time, further ensuring the quality of the coating. Finally, in the subsequent processing stage, the performance of the cladding coating and whether it meets the design requirements are fully verified by cleaning the residual powder and impurities, checking the coating surface quality, and performing performance tests. These steps not only ensure the neatness and beauty of the coating, but also provide a reliable basis for the practical application of the coating through performance test data.

[0079] A rare earth-containing SiC particle-reinforced Ni-based wear-resistant laser cladding coating is prepared by the above-mentioned preparation method.

[0080] Embodiment 1: A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, comprising the following steps:

[0081] Ni60A is mixed with SiC ceramic powder and Y2O3 powder in proportion. The mass percentage of the alloy powder components is: C: 0.5wt.%; B: 2.5wt.%; Cr: 15wt.%; Si: 4.2wt.%; Mo: 3wt.%; SiC: 10wt.%, Y2O3: 0.4wt.%, and the balance is Ni. The particle size range of the alloy powder is 45-100μm, and the particle size range of Y2O3 is 1-3μm. After mixing the powder, put it into a ball mill and stir it thoroughly. The speed of the ball mill is 150r / min. Mill for more than 4h and dry it in a drying oven at 60℃ for 30min.

[0082] The Q345 steel substrate was polished to remove the oxide layer. Specifically, the surface of the substrate was polished with 180#, 400#, and 600# sandpapers in turn to remove the oxide scale, and then cleaned with anhydrous ethanol and acetone.

[0083] The mixed powder was mixed with a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a ratio of 1:10 and then pre-prepared on the surface of the pre-treated Q345 steel substrate to form a prefabricated layer (thickness of 1.5 mm), and then naturally air-dried for 24 hours. Then, a rare earth-containing SiC-reinforced Ni-based wear-resistant laser cladding coating was obtained by laser cladding, wherein the laser power of the laser cladding was 1200 W, the scanning speed was 6 mm / s, the overlap rate was 45%, and the spot diameter was 2 mm. The protective gas was Ar gas, and the gas flow rate was 8 L / min.

[0084] In this example, the cladding layer after laser cladding was polished with high-magnification sandpaper to the metallographic requirements, and the microstructure of the cladding layer surface was obtained by scanning electron microscopy. Figure 1 The microhardness of the cladding layer was measured using a HV-1000A microhardness tester. The surface hardness of the coating and the metal substrate was measured after a load of 300 gf for 15 seconds. The average microhardness of the Q345 steel substrate is 223.57 HV 0.3 , compared with the substrate, the average hardness of the cladding coating is 822.13HV 0.3 , which is 3.68 times that of the substrate.

[0085] Embodiment 2: A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, comprising the following steps:

[0086] Ni60A is mixed with SiC ceramic powder and Y2O3 powder in proportion. The mass percentage of the alloy powder components is: C: 0.7wt.%; B: 2.7wt.%; Cr: 17wt.%; Si: 4.5wt.%; Mo: 2.8wt.%; Si C: 15wt.%, Y2O3: 0.8wt.%, and the balance is Ni. The particle size range of the alloy powder is 45-100μm, and the particle size range of Y2O3 is 1-3μm. After mixing the powder, put it into a ball mill and stir it thoroughly. The speed of the ball mill is 150r / min. Mill for more than 4h and dry it in a drying oven at 60℃ for 30min.

[0087] The Q345 steel substrate was polished to remove the oxide layer. Specifically, the surface of the substrate was polished with 180#, 400#, and 600# sandpapers in turn to remove the oxide scale, and then cleaned with anhydrous ethanol and acetone.

[0088] The mixed powder was mixed with a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a ratio of 1:10 and evenly pre-placed on the surface of the pre-treated Q345 steel substrate to form a prefabricated layer (thickness of 1.2 mm), and then naturally air-dried for 24 hours. Then, a rare earth-containing SiC-reinforced Ni-based wear-resistant laser cladding coating was obtained by laser cladding, wherein the laser power of the laser cladding was 1500W, the scanning speed was 8mm / s, the overlap rate was 45%, and the spot diameter was 2mm. The protective gas was Ar gas, and the gas flow rate was 6L / min.

[0089] The microhardness of the cladding layer was measured using a HV-1000A microhardness tester. The surface hardness of the coating and the metal substrate was measured after a load of 300 gf for 15 seconds. The average microhardness of the Q345 steel substrate is 223.57 HV 0.3 , compared with the substrate, the average hardness of the cladding coating is 904.82HV 0.3 , which is 4.05 times that of the substrate.

[0090] Embodiment 3: A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, comprising the following steps:

[0091] Ni60A is mixed with SiC ceramic powder and Y2O3 powder in proportion. The mass percentage of the alloy powder components is: C: 0.7wt.%; B: 2.6wt.%; Cr: 16wt.%; Si: 4.5wt.%; Mo: 2.6wt.%; Si C: 20wt.%, Y2O3: 1.2wt.%, and the balance is Ni. The particle size range of the alloy powder is 45-100μm, and the particle size range of Y2O3 is 1-3μm. After mixing the powder, put it into a ball mill and stir it thoroughly. The speed of the ball mill is 150r / min. Mill for more than 4h and dry it in a drying oven at 60℃ for 30min.

[0092] The Q345 steel substrate was polished to remove the oxide layer. Specifically, the surface of the substrate was polished with 180#, 400#, and 600# sandpapers in turn to remove the oxide scale, and then cleaned with anhydrous ethanol and acetone.

[0093] The mixed powder was mixed with a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a ratio of 1:10 and evenly pre-placed on the surface of the pre-treated Q345 steel substrate to form a prefabricated layer (thickness of 1 mm), and then naturally air-dried for 24 hours. Then, a rare earth-containing SiC-reinforced Ni-based wear-resistant laser cladding coating was obtained by laser cladding, wherein the laser power of the laser cladding was 1800W, the scanning speed was 8mm / s, the overlap rate was 45%, and the spot diameter was 2mm. The protective gas was Ar gas, and the gas flow rate was 10L / min.

[0094] The microhardness of the cladding layer was measured using a HV-1000A microhardness tester. The surface hardness of the coating and the metal substrate was measured after a load of 300 gf for 15 seconds. The average microhardness of the Q345 steel substrate is 223.57 HV 0.3 , compared with the substrate, the average hardness of the cladding coating is 1190.96HV 0.3 , which is 5.32 times that of the substrate.

[0095] Embodiment 4: A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, comprising the following steps:

[0096] Ni60A is mixed with SiC ceramic powder and Y2O3 powder in proportion. The mass percentage of the alloy powder components is: C: 0.4wt.%; B: 2.6wt.%; Cr: 16wt.%; Si: 4wt.%; Mo: 2.7wt.%; SiC: 30wt.%, Y2O3: 1.6wt.%, and the balance is Ni. The particle size range of the alloy powder is 45-100μm, and the particle size range of Y2O3 is 1-3μm. After mixing the powder, put it into a ball mill and stir it thoroughly. The speed of the ball mill is 150r / min. Ball mill for more than 4h and dry it in a drying oven at 60℃ for 30min.

[0097] The Q345 steel substrate was polished to remove the oxide layer. Specifically, the surface of the substrate was polished with 180#, 400#, and 600# sandpapers in turn to remove the oxide scale, and then cleaned with anhydrous ethanol and acetone.

[0098] The mixed powder was mixed with a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a ratio of 1:10 and evenly pre-placed on the surface of the pre-treated Q345 steel substrate to form a prefabricated layer (thickness of 1.4 mm), and then naturally air-dried for 24 hours. Then, a rare earth-containing SiC-reinforced Ni-based wear-resistant laser cladding coating was obtained by laser cladding, wherein the laser power of the laser cladding was 2000 W, the scanning speed was 8 mm / s, the overlap rate was 45%, and the spot diameter was 2 mm. The protective gas was Ar gas, and the gas flow rate was 7 L / min.

[0099] The microhardness of the cladding layer was measured using a HV-1000A microhardness tester. The surface hardness of the coating and the metal substrate was measured after a load of 300 gf for 15 seconds. The average microhardness of the Q345 steel substrate is 223.57 HV 0.3 , compared with the substrate, the average hardness of the cladding coating is 1245.37HV 0.3 , which is 5.57 times that of the substrate.

[0100] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, characterized in that: The following steps are involved: S10, powder preparation, ball milling and mixing Ni-based alloy powder, SiC particles, and alloy elements such as C, B, Cr, Si, Mo, and rare earth Y2O3 added in a certain proportion to ensure that the powder is evenly dispersed, and drying to prevent the powder from agglomerating; S20, substrate pretreatment, using 180#, 400#, 600# sandpaper to polish the steel substrate surface step by step to remove the oxide scale and rough layer, and then cleaning with anhydrous ethanol and acetone to obtain a clean and oil-free substrate surface; S30, powder coating, using a binder prepared by mixing ethyl cellulose and anhydrous ethanol in a specific ratio, evenly coating the mixed powder on the surface of the substrate, and then air-drying it naturally for 24 hours; S40, laser cladding, set the laser process parameters, including laser power 1200-2000W, scanning speed 6-8mm / s, overlap rate 45%, spot diameter 2mm, use Ar gas protection, and prepare a dense wear-resistant coating on the substrate surface through laser cladding technology.

2. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 1, characterized in that: The step S10 specifically includes the following steps: S101, material preparation, accurately weighing Ni-based alloy powder, SiC particles, C, B, Cr, Si, Mo and other alloy element powders and rare earth Y2O3 according to the predetermined mass percentage, ensuring that all materials are of high purity to avoid the influence of impurities on the coating performance; S102, ball milling and mixing, putting weighed various powder materials into a ball mill, adding an appropriate amount of ball milling media such as stainless steel balls or ceramic balls, setting parameters such as the speed of the ball mill, ball milling time and ball-to-material ratio, generally, the speed of the ball mill will affect the degree of powder refinement and mixing uniformity, and the ball milling time determines the degree of mixing sufficiency, starting the ball mill for mixing, during the ball milling process, collision and friction occur between the ball milling media and the powder, so that the powder is gradually refined and evenly mixed, and the ball milling effect is regularly checked to ensure that the powder is evenly mixed and reaches the required particle size requirements; S103, drying treatment, taking out the mixed powder after ball milling from the ball mill jar and drying it. The purpose of drying is to remove moisture and other volatile substances in the powder to prevent the powder from agglomerating during subsequent processing. The drying treatment can be carried out in an oven, and appropriate temperature and time are set. The temperature should not be too high to avoid oxidation or deterioration of the powder; the time should be long enough to ensure that the powder is completely dry. The dried powder should be stored in a dry, cool, ventilated place to avoid moisture and contamination; S104, quality inspection, conduct quality inspection on the mixed powder after drying, including indicators such as particle size distribution, mixing uniformity, and impurity content. If necessary, the powder can be screened or ball-milled again to meet the requirements of subsequent processing.

3. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 2, characterized in that: The percentage composition of each part in step S101 is: C: 0.4-0.7wt.%, B: 2.5-2.7wt.%, Cr: 15-17wt.%, Si: 4-4.5wt.%, Mo: 2.6-3wt.%, SiC: 10-30wt.%, and the remainder is Ni, wherein the addition amount of Y2O3 is 0.4-1.6wt.% of the total mass of the alloy powder.

4. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 2, characterized in that: The particle size range of the alloy element powder is 45-100 μm, and the particle size range of Y2O3 is 1-3 μm.

5. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 1, characterized in that: The step S20 specifically includes the following steps: S201, preliminary grinding, use 180# sandpaper to perform preliminary grinding on the surface of Q345 steel substrate. This step is mainly to remove large particles of impurities, thick oxide scale and obvious rough layer on the surface. When grinding, the force should be uniform and carried out in a certain direction to avoid leaving obvious scratches on the surface of the substrate; S202, medium grinding. After the initial grinding, use 400# sandpaper for medium grinding. The purpose of this step is to further refine the surface of the substrate and remove the fine scratches and residual oxide skin left in the previous step. It is also necessary to maintain uniform strength and consistent direction for grinding. S203, fine grinding, use 600# sandpaper for fine grinding. This step is to obtain a smoother and cleaner substrate surface, providing a good foundation for subsequent coating adhesion. When fine grinding, special attention should be paid to controlling the strength and speed to avoid excessive grinding and causing damage to the substrate surface; S204, degreasing and cleaning. After polishing, impurities such as oil, dust, etc. may remain on the surface of the substrate. First, use anhydrous ethanol to clean the surface of the substrate to remove oil and organic impurities. Anhydrous ethanol has good solubility and volatility, and can quickly and effectively remove oil without leaving any residue on the surface of the substrate. S205, deep cleaning, use acetone to deep clean the surface of the substrate. Acetone can further remove tiny impurities and residues on the surface to ensure that the surface of the substrate is clean and free of dirt. When cleaning, use a soft cloth or cotton swab to dip in an appropriate amount of acetone and gently wipe the surface of the substrate. Be careful not to use excessive force to scratch the surface of the substrate; S206. Drying treatment: After cleaning, the substrate should be placed in a ventilated place to dry naturally, or clean compressed air should be used to blow dry the surface moisture. Only after the substrate surface is completely dry can subsequent coating treatment be carried out.

6. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 1, characterized in that: In step S20, the steel substrate is Q345 steel.

7. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 1, characterized in that: The step S30 specifically includes the following steps: S301, preparing the binder. First, two main materials, ethyl cellulose and anhydrous ethanol, need to be prepared. Ethyl cellulose is the main component of the binder, and anhydrous ethanol is the solvent. The amounts of ethyl cellulose and anhydrous ethanol are accurately calculated according to specific ratio requirements. This ratio is the key to ensure stable performance of the binder and good coating effect. The calculated ethyl cellulose is gradually added to the anhydrous ethanol while stirring until the ethyl cellulose is completely dissolved to form a uniform and transparent binder solution. S302, powder mixing, prepare the powder material to be coated and ensure that it is mixed evenly without agglomeration, gradually add the prepared binder solution to the powder, stir with an appropriate tool such as a stirrer while adding, so that the powder and the binder are fully mixed evenly, and the stirring speed and time should be controlled during the mixing process to avoid generating too many bubbles or destroying the powder particles; S303, apply powder, ensure that the surface of the substrate has been pre-treated, clean, flat and free of oil. If there is dust or impurities on the surface of the substrate, it should be cleaned with a clean cloth or compressed air first, and use appropriate coating tools such as brushes, spray guns, etc. to evenly apply the mixed powder on the surface of the substrate. When applying, a certain thickness and uniformity should be maintained to avoid missing or uneven thickness. For large-area or complex-shaped substrates, multiple coatings or coating at different angles may be required to ensure the coating effect; S304, natural air drying, place the powder coated substrate in a well-ventilated place away from direct sunlight for natural air drying, ensure the air drying environment is clean and dust-free to avoid contamination of the coating. According to the requirements, the substrate is naturally air dried for 24 hours. This time is the key to ensure that the coating is fully dried, cured and reaches the predetermined performance. During the air drying process, the state of the coating should be checked regularly to ensure that there is no cracking, peeling, etc.

8. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 7, characterized in that: The ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1:10, wherein the coating thickness is 1-1.5 mm.

9. The method for preparing a rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating according to claim 1, characterized in that: The step S40 specifically includes the following steps: S401. In the preparation stage, ensure that the laser, gas protection system and other equipment are in good working condition without faults or abnormalities. According to the characteristics of the coating material and the substrate, set the power of the laser in the range of 1200-2000W. The specific value needs to be determined based on experiments or experience to achieve the best cladding effect. Set the scanning speed to 6-8mm / s. This speed range can ensure that the laser beam moves evenly on the surface of the substrate, while fully melting the powder and combining it with the substrate. Set the overlap rate to 45%. The overlap rate refers to the overlap between adjacent cladding passes, which is very important for ensuring the uniformity and density of the coating. Set the spot diameter to 2mm. The size of the spot directly affects the distribution of laser energy and the width of the cladding layer. Connect the Ar gas source and adjust the gas flow rate to an appropriate value to ensure that the cladding area is fully protected to prevent oxidation and impurity contamination. S402, laser cladding operation, according to the specific requirements of the coating material and the substrate, the substrate is preheated. Preheating can reduce the thermal stress in the cladding process and improve the bonding strength between the coating and the substrate, but preheating is not required in all cases. Start the laser according to the set process parameters, focus the laser beam on the substrate surface, the laser beam heats the substrate surface and the powder material, causing them to melt and mix rapidly, and the molten material solidifies rapidly on the substrate surface to form a dense, wear-resistant coating. Control the movement path and speed of the laser beam to ensure that the coating is uniform and defect-free. Perform multiple cladding passes according to the set overlap rate to ensure the thickness and uniformity of the coating. Monitoring and adjustment: During the cladding process, the cladding quality is monitored in real time through the control system to observe whether the coating surface is flat and whether there are defects such as cracks or pores. If necessary, adjust the laser process parameters in time to ensure the quality of the cladding layer. After the cladding is completed, let the coating cool naturally or use appropriate cooling methods to accelerate the solidification process. The control of the cooling rate has a certain influence on the performance of the coating and needs to be determined according to the specific situation. S403, follow-up treatment, clean the residual powder and impurities around the cladding area, check whether the coating surface is smooth and defect-free, and perform performance tests on the cladding coating, such as hardness, wear resistance, corrosion resistance, etc., to verify whether it meets the design requirements.

10. A rare earth-containing SiC particle reinforced Ni-based wear-resistant laser cladding coating, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.